CREST: a Climate Data Record of Stratospheric Aerosols - V. F. Sofieva; A. Rozanov; M. Szelag; J. P. Burrows; C. Retscher; R. Damadeo; D. Degenstein; L. A. Rieger; A. Bourassa (Earth System Science Data)
Climate-related studies need information about the distribution of stratospheric aerosols, which influence the energy balance of the Earth's atmosphere. In this work, we present a merged dataset of vertically resolved stratospheric aerosol extinction coefficients, which is derived using data from six limb and occultation satellite instruments: SAGE (Stratospheric Aerosol and Gas Experiment) II on ERBS (Earth Radiation Budget Satellite), GOMOS (Global Ozone Monitoring by Occultation of Stars) and SCIAMACHY (Scanning Imaging Spectrometer for Atmospheric Chartography) on Envisat, OSIRIS (Optical Spectrograph and InfraRed Imaging System) on Odin, OMPS (Ozone Monitor Profiling Suite Limb Profiler) on Suomi NPP, and SAGE III on the ISS (International Space Station).